Profile of UNIPÊ dentistry students on the use of intraoral device in patients with oral rehabilitation (Research, Society and Development, 2021)
This study was a descriptive, exploratory and quantitative research that aimed to analyze the perception and knowledge of Dentistry students at the University Center of João Pessoa - UNIPÊ, about the indication for the use of interocclusal devices in patients with oral rehabilitation. The sample consisted of 119 students from the 8th to the 10th period of the course. The instrument for data collection consists of a questionnaire which addressed whether students agreed on the relevance of using an interocclusal device in a patient with (TMD) and parafunctional habits after oral rehabilitation, and what the benefits were. Microsoft's Google Forms tool was used to approach the students, who were selected in a non-probabilistic way. Data were tabulated in an EXCEL spreadsheet and analyzed, according to data normality, with the aid of parametric or non-parametric tests, using the SPSS version 20.0 program, considering a 95% confidence level. It was also found that there was agreement among respondents that the use of the interocclusal device serves as an auxiliary treatment for temporomandibular disorders (n = 114; 95.8%), requiring the use of devices after a rehabilitative procedure in a patient who has or has already presented a picture of temporomandibular disorder (n = 92; 77.3%), as a complement to treatment (n = 69; 58.0%). It is concluded that, despite the results of the study being satisfactory, there is a lack of approach to the theme in the academic context, which consequently results in a deficit in the indications for this treatment after oral rehabilitation in a patient with TMD's.